2017
DOI: 10.1016/j.jse.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect and time course of extension and internal rotation stretching of the shoulder on infraspinatus muscle hardness

Abstract: The results suggested that shoulder extension and internal rotation SS effectively decreased the infraspinatus muscle's hardness. In addition, the results indicated that a period exceeding 20 seconds of SS decreased the infraspinatus muscle's hardness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…To the best of our knowledge, this is the first report to investigate the minimum SS duration required to decrease the passive *: p < 0.01: significant difference between PRE In this study, the final angle significantly increased after 300 s of SS, which is consistent with previous studies that investigated the acute effect of SS on ROM. In addition, our results showed that the minimum SS duration required to decrease the passive stiffness of the hamstring was >180 s. These results are consistent with previous studies that reported no significant changes in the passive stiffness of the hamstring after 20-90 s of SS 12,14) , but showed a decrease in the passive stiffness after >180 s 12,21,22) . Our finding suggests that the minimum SS duration required to decrease the passive stiffness of the hamstring may be between 120 s and 180 s. Therefore, future study is needed to investigate in detail whether an SS duration between 120 s and 180 s could decrease the passive stiffness of the hamstring.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first report to investigate the minimum SS duration required to decrease the passive *: p < 0.01: significant difference between PRE In this study, the final angle significantly increased after 300 s of SS, which is consistent with previous studies that investigated the acute effect of SS on ROM. In addition, our results showed that the minimum SS duration required to decrease the passive stiffness of the hamstring was >180 s. These results are consistent with previous studies that reported no significant changes in the passive stiffness of the hamstring after 20-90 s of SS 12,14) , but showed a decrease in the passive stiffness after >180 s 12,21,22) . Our finding suggests that the minimum SS duration required to decrease the passive stiffness of the hamstring may be between 120 s and 180 s. Therefore, future study is needed to investigate in detail whether an SS duration between 120 s and 180 s could decrease the passive stiffness of the hamstring.…”
Section: Discussionsupporting
confidence: 92%
“…The difference in the minimum SS duration between the gastrocnemius and hamstring might be because of the tension applied to muscle. The magnitude of the tension applied to the muscle is affected by muscle volume 22) . Because muscle volume of the hamstring muscle is larger than that of the gastrocnemius muscle 23) , tension applied to the hamstring muscle as per muscle volume was lower than that applied to the gastrocnemius muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest is that the stretching duration that immediately changes the muscle stiffness may differ in the target muscle. The stretching durations for 3 min, 2 min, 1 min, and 20 s were needed to change the muscle stiffness of the hamstrings (Nakamura et al, 2019), the gastrocnemius (Nakamura et al, 2013), the iliacus (Nojiri et al, 2019), and infraspinatus (Kusano et al, 2017), respectively. One of the factors that determine the stretching duration could be the muscle volume, more precisely, the cross-sectional area of the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…First, whether the stretching duration for 30 s is the minimum time to decrease the shear modulus of the pectoralis minor is unclear. A previous study used a stretching minimum duration of 20 s for the infraspinatus muscle (Kusano et al, 2017). We decided on a stretching duration of 30 s because of its practical use in rehabilitation and sport practice, although the minimum stretching duration could be shorter than 30 s for PMi.…”
Section: Discussionmentioning
confidence: 99%
“…Stretching is useful for increasing flexibility in clinical and athletic situations. Many previous studies have reported on the effects of stretching 7,9,11,18,26 but few studies have reported the method or position used to create an effective stretch 24,30 . Because the shoulder joint has multiple degrees of freedom and a large range of motion, the method used to stretch shoulder muscles needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%